2019
DOI: 10.3390/ijerph16081334
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and Environmental Risk Factors Influencing the Inducement of Erythema among Nigerian Laboratory University Workers with Multiple Chemical Exposures

Abstract: : The chemicals from laboratories pose a significant risk forinducing erythema, an abnormal redness of the skin, as a result of poor occupational and environmental factors that promote hypersensitivity to a chemical agent. The aim of this present study was to determine the occupational and environmental risk factors influencing the inducement of erythema in laboratory workers due to exposure to chemicals. This was a cross-sectional study on a population-based sample of Nigerian university laboratory workers. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The measurement principle was based on the absorption peak of haemoglobin at 660 nm wavelengths. Skin erythema, commonly known as a flare, is the reddening response of skin upon exposure to external stimuli such as an allergen [53], or UV radiation [51,53]. Our results indicated that RC supplementation effectively reduces participants' EI.…”
Section: Discussionmentioning
confidence: 62%
“…The measurement principle was based on the absorption peak of haemoglobin at 660 nm wavelengths. Skin erythema, commonly known as a flare, is the reddening response of skin upon exposure to external stimuli such as an allergen [53], or UV radiation [51,53]. Our results indicated that RC supplementation effectively reduces participants' EI.…”
Section: Discussionmentioning
confidence: 62%
“…Implementing effective environmental controls ensures that chemical laboratories maintain a safe and conducive working environment for laboratory personnel and the research being conducted. By investing in proper ventilation, temperature control, and other environmental measures, laboratories can reduce the risk of accidents, protect valuable experiments, and promote a culture of safety and excellence. …”
Section: Environmental Controlsmentioning
confidence: 99%